A Mixed-Methods Study of Community Health Worker Roles in Malaria Policy Implementation and Control - Sulistyarini, Wahyu Dewi; Anam, Khoirul; Waluyo, Harjito Ponco (Chakra Brahmanda Lentera Institute, 2026)
Background: Malaria elimination increasingly depends on effective community-based interventions, particularly in high-mobility settings such as Indonesia’s New Capital (IKN). However, limited evidence exists on how malaria cadre policies are translated into frontline practice in rapidly changing development contexts. This mixed-methods study aimed to analyze the role of malaria cadres in malaria case identification and evaluate malaria cadre policy implementation in the IKN development area by integrating quantitative performance assessment with qualitative exploration of implementation experiences. Methods: This explanatory sequential mixed-methods study followed the GRAMMS reporting guideline. A validated instrument assessed all 61 active malaria cadres using total population sampling. Quantitative findings informed qualitative interviews and focus group discussions with key stakeholders. Data were integrated during interpretation and analyzed using descriptive statistics and thematic analysis. Results: The instrument demonstrated excellent validity and reliability (Cronbach’s α = 0.86). Quantitative findings showed the highest performance in behavior change communication (mean = 1.96), environmental risk monitoring (mean = 1.91), and malaria screening (mean = 1.87), whereas malaria treatment showed the lowest performance (mean = 1.38). Qualitative analysis identified four themes, revealing that malaria cadres functioned as adaptive frontline responders with strong engagement in case detection and community interaction but limited preventive and planning roles. Integrated findings demonstrated complementarity, with qualitative evidence explaining variations in quantitative performance across cadre role domains. Conclusion: Integrated findings indicate that malaria cadres are effective frontline responders but require stronger preventive support, supervision, and policy integration to sustain malaria elimination in high-mobility settings.